Play-Based Psychoeducation to Enhance Emotional Literacy Among Migrant Children in Malaysia - Rahmayanti, Ristina Putri; Wilandika, Angga; Widianti, Anggriyana Tri (Journal of Public Health Sciences, 2025)
Emotional literacy is critical for children’s psychosocial well-being and particularly challenging among migrant children facing displacement and cultural stressors. This pre-experimental study evaluated the immediate changes of a play-based psychoeducation program on emotional literacy among 30 Indonesian migrant children aged 9–15 years in Malaysia. Using a one-group pretest–posttest design, participants completed the validated Emotional Literacy Questionnaire before and after intervention. Wilcoxon signed-rank tests showed a significant improvement in total emotional literacy scores from 11.53 ± 0.54 to 13.30 ± 0.49 (p = 0.009, r = 0.47). Children improved in recognizing emotions, applying emotional knowledge to case studies, and employing adaptive regulation strategies. The findings provide preliminary evidence suggesting that culturally congruent, play-based psychoeducation may support improvements in emotional competence among migrant children. Nursing professionals can incorporate such interventions to promote psychosocial adaptation in school and community settings.